Programas televisivos de contenido violento y su impacto en el comportamiento psicosocial de los niños del Barrio Victoria Vallejo, del cantón Valencia, año 2020 - Zarabia Gil, Nathaly Rashel (2021)
This research work is aimed at carrying out a study on television programs with violent content and their impact on the psychosocial behavior of children in the Victoria Vallejo neighborhood, in the canton of Valencia. And in this way to analyze the psychosocial behavior of the children of the Victoria Vallejo neighborhood. The research analyzed the impact of television programs with violent content on the psychosocial behavior of children from the Victoria Vallejo neighborhood, in the canton of Valencia, in 2020. It plays an important role in the social life of children, considering that it is part of practically all homes, not only as an information or entertainment medium, even as a cultural or learning medium, because it is an element that can even modify customs . It is essential that parents or adults who are in charge, instruct the child every time he is exposed to television broadcasts that have violent content, creating in them good habits and positive learning so that they can distinguish the good and bad of television.